Pemanfaatan Crowdfunding Syariah Untuk Pembiayaan Proyek Sosial Dan Ekonomi Berkelanjutan di Kabupaten Sumbawa - Feri Irawan (Indra Institute Research & Publication, 2024)
This research examines the utilization of Islamic crowdfunding for financing sustainable social and economic projects in Sumbwa. Islamic crowdfunding is a fundraising method based on Islamic sharia principles that offers an alternative solution in financing projects with positive social and economic impacts. Through a descriptive qualitative approach, data was collected through in-depth interviews, participatory observation, and document study. The results showed that Islamic crowdfunding has increased access to inclusive and fair financing for MSMEs and social projects. In addition, community participation in Islamic crowdfunding is quite high, with significant contributions in funding sustainable projects. Projects funded through these platforms provide not only economic but also social benefits, such as improving people's quality of life and supporting the Sustainable Development Goals (SDGs). However, the study also identified challenges in the implementation of Islamic crowdfunding, including inadequate regulations and lack of public understanding. In conclusion, Islamic crowdfunding has great potential to support the financing of sustainable social and economic projects in Sumbawa, but it requires regulatory support and wider public education to optimize its benefits. Collaboration between the government, crowdfunding platforms, and the public is essential to create an ecosystem that supports the growth of Islamic crowdfunding.